IMPROVING THE CONTENT OF GENERAL LAW DISCIPLINES AS A CONDITION FOR FORMING THE CREATIVE POTENTIAL OF A FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2010)
This article is devoted to defining of optimum terms of successful development of crea tive potential of future teachers by the theoretical ground of the necessary improvement of maintenance of the general law disciplines.